Building e-Loyalty towards Online Food Delivery Apps: A Serial-Mediation Model - Ella Mittal; Navneet Kaur (Asian Academy of Management Journal, 2023)
This study analysed the mechanism to generate e-loyalty among customers through e-service quality regarding OFD (OFD) apps. It examined the indirect influence of e-service quality on e-loyalty through the mediation of e-trust and e-satisfaction of customers. The serial mediation approach was used to test the proposed model of the study. Data was obtained through a self-administered structured questionnaire filled by 261 respondents from north India. The model hypotheses were tested by applying variance-based partial least squares in software SmartPLS 3. All the results were found to be statistically significant, and all proposed hypotheses were accepted. The results revealed that e-service quality positively contributed to building e-loyalty among customers of OFD apps. Furthermore, the results of the mediation effect suggested that e-trust and e-satisfaction strengthened the relationship between e-service quality and customers’ e-loyalty and therefore, that restaurants using OFD apps should try to provide the best online services to build trust along with satisfaction among their customers to increase loyalty to their online platforms. Theoretical implications for scholars and practical implications for the marketer are discussed.